2014
DOI: 10.4103/0976-9668.127275
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory infections among under-5 children in India: A situational analysis

Abstract: Acute respiratory infections (ARIs) are the leading cause of death among children less than 5 years in India. Emergence of newer pathogenic organisms, reemergence of disease previously controlled, wide spread antibiotic resistance, and suboptimal immunization coverage even after many innovative efforts are major factors responsible for high incidence of ARI. Drastic reduction in the burden of ARI by low-cost interventions such as hand washing, breast feeding, availability of rapid and feasible array of diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 34 publications
2
60
0
3
Order By: Relevance
“…About 11.9 million episodes of severe and 3.0 million episodes of very severe acute lower respiratory infections (ALRI) result in hospital admissions in young children worldwide . India is predicted to have over 700 million episodes of ARI and 52 million episodes of pneumonia per year . Respiratory infections and illnesses in children thus form a substantial disease burden in emergency care, outpatients, and hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%
“…About 11.9 million episodes of severe and 3.0 million episodes of very severe acute lower respiratory infections (ALRI) result in hospital admissions in young children worldwide . India is predicted to have over 700 million episodes of ARI and 52 million episodes of pneumonia per year . Respiratory infections and illnesses in children thus form a substantial disease burden in emergency care, outpatients, and hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%
“…Acute respiratory infections are a major cause of morbidity and mortality among children [11,12]. Although respiratory infections are common in children, a specific diagnosis is rare.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that acute respiratory infections include a spectrum of severity, within which the majority of the milder infections may go undetected, due to the lack of uniformity of illness definition and misclassification errors. Thus, the incidence of respiratory infections can be based reliably on only community‐based longitudinal cohorts rather than hospital‐based studies . And with regard to asthma, few studies have reported incidence rates for pediatric asthma in the general population.…”
Section: Discussionmentioning
confidence: 99%